2021
DOI: 10.1021/acsomega.1c01365
|View full text |Cite
|
Sign up to set email alerts
|

In Situ SAXS and WAXD Investigations of Polyamide 66/Reduced Graphene Oxide Nanocomposites During Uniaxial Deformation

Abstract: Epitaxial crystallization between Polyamide 66 (PA66) and reduced graphene oxide (RGO) can enhance the interfacial interaction and the mechanical properties of PA66/RGO nanocomposites. In situ two-dimensional synchrotron radiation wide angle X-ray diffraction and small angle X-ray scattering were used to track the structural evolution of the PA66/RGO nanocomposites with an epitaxial crystal during uniaxial deformation. In the PA66/RGO nanocomposites, the structural evolution of non-epita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 55 publications
1
3
0
Order By: Relevance
“…Based on the calculation result, the crystal plane space of GO was 0.78 nm. The 2 θ diffraction angle of GO appeared at the position of 11.3°, which was similar to the literature reported 55 . The (001) crystal plane spacing of GO was 0.782 nm, larger than that of 0.336 nm graphite.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Based on the calculation result, the crystal plane space of GO was 0.78 nm. The 2 θ diffraction angle of GO appeared at the position of 11.3°, which was similar to the literature reported 55 . The (001) crystal plane spacing of GO was 0.782 nm, larger than that of 0.336 nm graphite.…”
Section: Resultssupporting
confidence: 88%
“…The 2θ diffraction angle of GO appeared at the position of 11.3 , which was similar to the literature reported. 55 The (001) crystal plane spacing of GO was 0.782 nm, larger than that of 0.336 nm graphite. The main reason could be the weakened van der Waals' force sourced from sheets and the increased layer space the intervention of oxygenated groups during the GO preparation process.…”
Section: Xrd Characterizationmentioning
confidence: 91%
“…On the other hand, the γ -type crystal form in a pseudo-hexagonal shape is the other stable crystalline structure of PA66, which was formed with shorter molecular chains. The introduction of PACM6 disrupted the crystalline regularity of PA66, leading to a reduction in the copolymer’s crystallinity and resulting in a transition from the monoclinic α -type to the pseudo-hexagonal γ -type crystalline structure [ 41 , 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, the hydrophilicity of GA/PA66 films was significantly increased since the composite films had a super hydrophilic surface of 0° at both 0 s and 3 s. Similar results were reported by Cao et al [43], who found that compared to pure polyethersulfone film, the hydrophilicity of the polyethersul-fone/PA66 filtration film surface was improved. This may be related to the fact that a considerable number of hydrophilic groups existed in PA66 [44], and the homogeneous dispersion of gelatin in the mixing system, thus exposing the hydrophilic groups more sufficiently to the surface. The hydrophilic surfaces of materials have been considered as an important factor in increasing the antimicrobial agent loading and antimicrobial activity.…”
Section: Water Contact Angles Analysismentioning
confidence: 99%